Study on the determinants of export in textiles and apparels in Malaysia / Irniza Ismail (Faculty of Business and Management, 2007)
The constant or stagnant of export in textiles and apparels in Malaysia is increasingly become a concern for the future of the textiles and apparels industry in Malaysia. Since textiles and apparels industry is a big industry and also one of the major contributors in the Malaysian economy, the constant growth can give an impact not just to the Malaysian economy but also to the exporter and future exporter itself. Besides that, the replacement of Multi Fibre Agreement (MFA) at 1 January 2005 to the Agreement of Textiles and Clothing (ATC), bring much problem to the Malaysian textiles and apparels as ATC has demolished all the quotas and this create an advantage to the Chinese textiles and apparels because they have high quality materials as well as low in labour costs. This will make other countries import more from China since they can provide the goods in much more cheaper but with high quality. The purpose of this study is to verify the determinants of export in textiles and apparels in Malaysia. Other than that, this study is also conducted in order to find out the trend of the export sales of the textiles and apparels in Malaysia from 1986 - 2005. Furthermore, this study also wants to know whether the exchange rate, gross domestic product, labour costs and population have a direct influence in the export sales of textiles and apparels in Malaysia. This study is descriptive research so because that, this study will be gathering secondary data rather than primary data. The study will be using internet, newspaper, magazines and past research as a method in gathering the data that is applicable to the study and also in understanding the export of textiles and apparels in Malaysia. There